Rightful Way of Banking. - Masood, Omar (Cambridge Scholars Publishing, 2015)
It has taken over five centuries for banking to evolve to its present state, and the concept of ""interest"" is undoubtedly the life-blood of the whole financial system. Interest was religiously prohibitive for centuries in several faiths, such as Buddhism and Hinduism, Judaism, Christianity and, Islam, and was also strongly opposed by neo-classical economists in the 1930s. Interest (riba) is still outlawed in Islam, with the term ""riba-eater"" being one of the cruellest insults. Islamic scholars have explained that the current practice of contracts without interest is a result of following t